Picture them dead - Bonner, Brynn, 1950- (Bonner, Brynn, 1950- Family history mystery, 2015)
In this third cozy whodunit in the Family History Mystery series, a professional genealogist duo searches for the link between a death from long ago and a modern-day murder. As a professional genealogist, I?ve seen enough skeletons come dancing out of closets to get a respectable conga line formed up. But they?ve always been metaphorical skeletons. Until today. When genealogists Sophreena McClure and Esme Sabatier are called on by Detective Jenny Jeffers to help figure out who the corpse in the backyard of her father's house is, they reluctantly agree. Known for figuring out the unusual, Sophreena and Esme do their best to uncover the mystery behind the corpse, and the glass coffin he's buried in. Word soon spreads about the bizarre burial site, leading the people of Morningside to "adopt" the corpse and begin leaving mementos in memoriam for him. But when the body of a young woman is found near the memorial, the duo has another task on their hands: to dig into the past of the house's previous owners. Could the clues to a recent murder finally help this soul rest in peace?